Aphaereta minuta Nees 1811 ... - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Aphaereta minuta (Nees, 1811) Distribution in Iran. Isfahan (Ghahari et al. 2011c as Asobara minuta; Khajeh et al. 2014), Tehran (Khajeh et al. 2014). Distribution outside Iran. Widely distributed and frequent to common in the Palaearctic region (Papp 2007a), and almost all of Europe (Fischer 1973a). Austria, Azores, Bulgaria, Canary Islands, Croatia, Czech Republic, Faeroe Islands, Finland, France, Germany, Greenland, Hungary, Iceland, Italy, Juan Fernandez Islands, Moldova, Morocco, Netherlands, Poland, Romania, Slovenia, Sweden, Switzerland and Uzbekistan (Yu et al. 2012), Greece (Papp 2007a as Asobora minuta; Yu et al. 2012), Korea (2007b; Yu et al. 2012), Madeira Islands (van Achterberg and Aguiar 2009; Yu et al. 2012), Russia (Lelej 2012; Yu et al. 2012), Serbia (Žikić et al. 2000; Yu et al. 2012), Spain (Docavo et al 1985, Tormos 1987; Yu et al. 2012), United Kingdom (Broad et al. 2012; Yu et al. 2012). Host records. This species is reported as a polyphagous gregarious larval-pupal parasitoid of fly ... : Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on page 4, DOI: 10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961 ...